Drug Therapy and Substance-Related Disorders - Libal, Joyce, author (Philadelphia : Mason Crest Publishers, 2004)
Describes the characteristics and drug treatment of disorders related to substance abuse, including alcoholism and other addictions to legal and illegal drugs